Stolen Youth: Case Study on Psychological Effects of Parental Separation - Collantes, Kalaya Enyana; Aurelia, Desree Jan; Castillo, Joemarc Jr.; Mangalindan, Grethel Faye; Nicolas, Deilayah Vasnie; Villarama, Joseph (Journal of Interdisciplinary Perspectives, 2024)
Family is the cradle of every person. It builds a foundation or core principles that a person carries throughout life. This study focuses on an in-depth investigation of the parent-child relationship, mental health, and academic life of a student with separated parents. This qualitative research was approached using a case study model and purposive sampling technique with one subject, after which semi-structured interviews were conducted through Google Meet, and then finally, results were analyzed thematically. Results revealed seven main themes with corresponding subthemes, such as, but not limited to, early independence, loss of a mother figure, and personal and academic life overlap. The parental separation negatively affected the subject, shown through depression, anxiety, abandonment and trust issues, exclusion, emotional isolation, self-harm attempts, and suicidal ideations. Negative impacts were also placed on the subject’s interest in building a future family, affecting academic life, as the subject unhealthily copes with being dismissive of emotions. The subject lost contact with their mother, leaving the residential father as the only parent figure; hence, he needs a genuine and comfortable environment, especially family-wise. Nonetheless, the subject could use the circumstances as fuel to succeed. The findings provide grounds for further research on the psychological effects of parental separation on students while emphasizing the importance of giving undivided attention to children during such a challenging time.